(3ESJQGJjLjGJ GdJZjjQs - (3SYjO jS(B, (3YGeQs ((3GdbGgQI(B:s (3eQcR hGjO SjQajS ddESJTGQGJ hGdJWhjQ GdEOGQj(B,s, 1994)
(3edNUGJ HMhK hebGdGJ GdeDJeQ GdSfhj GdChd hGdKGfj hGdKGdK hGdQGHY, GdESdGe hGdEOGQI Hjf GdJZjjQ hGdJfXje hGdJWhjQ, Mhd GdCfJGLjI hbjGSgG ef CLd JMSjfgG, GdYhGed GdeDKQI Ydi GdBOGA GdhXjaj hGdEfJGLjI, EOGQI GdLhOI GdTGedI(B- (3LdSGJ GdEfWdGb GdacQj, GSJQGJjLjGJ EOGQI GdWGbI ceONd ef eOGNd GdJZjjQ, GdESJQGJjLjGJ hGdgjcdI(B- (3JMOjGJ GdJMhd ef GdbWGY GdYGe Gdi GdbWGY GdNGUs
Keywords: (3GdEOGQI(B- (3JWhjQs; (3GdJWhjQ GdEOGQjs; (3GdJZjjQs